Impact of water resource development on connectivity and primary productivity across a tropical river floodplain. Issue 4 (30th January 2022) - Molinari, Bianca; Stewart‐Koster, Ben; Malthus, Tim J.; Bunn, Stuart E.
Abstract: Floodplain wetlands provide an important subsidy for riverine food webs as sites of high algal production. However, this subsidy depends on the degree of landscape connectivity during flood pulses, which provides the opportunity for movement of higher order consumers between rivers and floodplains to access these productive habitats. Changes in floodplain inundation extent and duration, due to variable wet season flows or water resource development (WRD), can impact landscape connectivity and ultimately the magnitude of the food web subsidy. We explored landscape connectivity using graph theory and derived four new metrics to measure how different flow scenarios can affect connectivity and algal production. We considered a historic scenario with the present level of water resource development in our study area, the Mitchell River, and a WRD scenario with the inclusion of three new dams in the catchment. We generated 240 unique daily spatial graphs, using surface water inundation maps across 40‐day flood events to compare a dry year (2006), an average flow year (2001) and a wet year (2009) with and without a WRD scenario. Drier years and WRD scenario resulted in floodplain fragmentation, potentially constraining the movement of higher order consumers. Changes in connectivity due to WRD resulted in predicted reductions of up to 26% of algal production on the floodplain that was otherwise connected to the main river channels. Synthesis and applications . The approach developed in this study provides new metrics to identify how changes in floodplain surface water extent due to water resource development and climatic variation may impact ecosystem function such as connectivity that facilitates access of higher order consumers to primary production in floodplain wetlands. With a direct link to river flow alteration, these metrics can inform catchment planning and management to ensure that the conservation of floodplain ecosystem functions is adequately considered in water resource management decisions. Abstract : The approach developed in this study provides new metrics to identify how changes in floodplain surface water extent due to water resource development and climatic variation may impact ecosystem function such as connectivity that facilitates access of higher order consumers to primary production in floodplain wetlands. With a direct link to river flow alteration, these metrics can inform catchment planning and management to ensure that the conservation of floodplain ecosystem functions is adequately considered in water resource management decisions. Resumo: As planícies de inundação fornecem um subsídio importante para cadeias alimentares aquáticas em forma de produção primária. No entanto, esse subsídio depende do grau de conectividade da paisagem durante os pulsos de inundação, o que fornece a oportunidade para o movimento de consumidores entre rios e planícies de inundação para acessar esses habitats produtivos. Mudanças na extensão e duração da inundação da planície de inundação, devido a variações climáticas ou desenvolvimento dos recursos hídricos (DRH), podem impactar a conectividade da paisagem e, em última instância, a magnitude do subsídio de produtores primários para as cadeias alimentares. Exploramos a conectividade da paisagem usando a teoria dos grafos e derivamos quatro novas métricas para medir como os diferentes cenários de inundação podem afetar a conectividade e a produção primária. Consideramos um cenário histórico com o nível atual de desenvolvimento de recursos hídricos em nossa área de estudo, o Rio Mitchell, na Austrália, e um cenário DRH com a inclusão de três novas barragens na bacia hidrográfica. Geramos 240 gráficos diários, usando mapas de inundação em eventos de inundação de 40 dias para comparar um ano seco (2006), um ano de fluxo médio (2001) e um ano úmido (2009), nos cenários histórico e DRH. Anos mais secos e os cenários DRH resultaram na fragmentação da planície de inundação, potencialmente restringindo o movimento de consumidores. Mudanças na conectividade devido ao DRH resultaram em reduções previstas de até 26% da produção primária na planície de inundação que de outra forma estava conectada aos canais principais do rio Mitchell. Síntese e aplicações . Esta abordagem fornece novas métricas para identificar como as mudanças na extensão da água superficial da planície de inundação e na conectividade podem impactar o funcionamento do ecossistema, como o potencial acesso de consumidores de ordem superior à produção primária em áreas úmidas da planície de inundação. Com uma ligação direta à alteração da vazão do rio, essas métricas podem informar o planejamento e gestão da bacia para garantir que a conservação das funções do ecossistema da planície de inundação seja adequadamente considerada sob os impactos futuros da gestão dos recursos hídricos.